Penguatan Ketahanan Keluarga Sakinah Melalui Penyuluhan Hukum Perkawinan bagi Masyarakat Kelurahan Anggut Dalam - Putri Alafa; Ramlan Ramlan; Nurul Kholifah; Alsi Nopita Sari; Najwa Bilaiska; Chairul Guntur Ramadhan; Ova Lara Sintia; Putri Dewi Maratus Sari’ah; Muhammad Faheru Santosa; Ahmad Habibillah; Hadi Aiman Shafiq; Muhammad Rahmat Tata; Rafli Ravendo (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The family is the smallest social unit that plays a vital role in shaping the quality of human resources and maintaining the stability of community life. However, various household problems such as family conflict, poor understanding of the rights and obligations of husband and wife, and lack of legal awareness can impact family resilience. Therefore, educational efforts are needed to improve public understanding of marriage law and the importance of building a harmonious family. This community service activity aims to strengthen the resilience of harmonious families through marital law counseling for the community of Anggut Dalam Village, Bengkulu City. The method used is Asset-Based Community Development (ABCD), which focuses on utilizing community assets and potential. The activity stages include discovery, dream, design, define, and destiny. The activity was implemented through material delivery, interactive discussions, and question-and-answer sessions regarding marriage law, the rights and obligations of husband and wife, the importance of marriage registration, and efforts to build a harmonious family. The results of the activity showed an increase in public understanding of the legal aspects of marriage and the importance of family resilience. The enthusiasm of the participants was evident in the high level of participation in the discussion and their ability to understand the material presented. This activity also encouraged growing public awareness to apply legal and religious values ​​in domestic life.